Fetal cerebral blood‐flow redistribution: analysis of Doppler reference charts and association of different thresholds with adverse perinatal outcome. (1st November 2021) - Wolf, H.; Stampalija, T.; Lees, C. C.; ,
ABSTRACT: Objectives: First, to compare published Doppler reference charts of the ratios of flow in the fetal middle cerebral and umbilical arteries (i.e. the cerebroplacental ratio (CPR) and umbilicocerebral ratio (UCR)). Second, to assess the association of thresholds of CPR and UCR based on these charts with short‐term composite adverse perinatal outcome in a cohort of pregnancies considered to be at risk of late preterm fetal growth restriction. Methods: Studies presenting reference charts for CPR or UCR were searched for in PubMed. Formulae for plotting the median and the 10 th percentile (for CPR) or the 90 th percentile (for UCR) against gestational age were extracted from the publication or calculated from the published tables. Data from a prospective European multicenter observational cohort study of singleton pregnancies at risk of fetal growth restriction at 32 + 0 to 36 + 6 weeks' gestation, in which fetal arterial Doppler measurements were collected longitudinally, were used to compare the different charts. Specifically, the association of UCR and CPR thresholds (CPR < 10 th percentile or UCR ≥ 90 th percentile and multiples of the median (MoM) values) with composite adverse perinatal outcome was analyzed. The association was also compared between chart‐based thresholds and absolute thresholds. Composite adverse perinatal outcome comprised both abnormal condition at birth and major neonatal morbidity. Results: Ten studies presenting reference charts for CPR or UCR were retrieved. There were large differences between the charts in the 10 th and 90 th percentile values of CPR and UCR, respectively, while median values were more similar. In the gestational‐age range of 28–36 weeks, there was no relationship between UCR or CPR and gestational age. From the prospective observational study, 856 pregnancies at risk of late‐onset preterm fetal growth restriction were included in the analysis. The association of abnormal UCR or CPR with composite adverse perinatal outcome was similar for percentile thresholds or MoM values, as calculated from the charts, and for absolute thresholds, both on univariable analysis and after adjustment for gestational age at measurement, estimated fetal weight MoM and pre‐eclampsia. The adjusted odds ratio for composite adverse perinatal outcome was 3.3 (95% CI, 1.7–6.4) for an absolute UCR threshold of ≥ 0.9 or an absolute CPR threshold of < 1.11 (corresponding to ≥ 1.75 MoM), and 1.6 (95% CI, 0.9–2.9) for an absolute UCR threshold of ≥ 0.7 to < 0.9 or an absolute CPR threshold of ≥ 1.11 to < 1.43 (corresponding to ≥ 1.25 to < 1.75 MoM). Conclusions: In the gestational‐age range of 32 to 36 weeks, adjustment of CPR or UCR for gestational age is not necessary when assessing the risk of adverse outcome in pregnancies at risk of fetal growth restriction. The adoption of absolute CPR or UCR thresholds, independent of reference charts, is feasible and makes clinical assessment simpler than if using percentiles or other gestational‐age normalized units. The high variability in percentile threshold values among the commonly used UCR and CPR reference charts hinders reliable diagnosis and clinical management of late preterm fetal growth restriction. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.